Impact of the level of adherence to the Mediterranean Diet on blood pressure: A systematic review and meta-analysis of observational studies. Issue 12 (December 2021) - Bakaloudi, Dimitra Rafailia; Chrysoula, Lydia; Leonida, Ioannis; Kotzakioulafi, Evangelia; Theodoridis, Xenophon; Chourdakis, Michail
Summary: Background: High blood pressure (BP) constitutes a common and serious medical condition which is rising globally, and is among preventable factors for cardiovascular, renal, brain and other diseases. Modifiable risk factors of high BP include unhealthy dietary patterns, presence of obesity, excess alcohol consumption and lack of physical activity. Data in regard to the different types of diets show that Mediterranean diet (MD) is associated with healthy levels of BP. In this study we aimed to investigate the impact of the level of adherence to MD in BP. Aims-methods: A systematic literature search (up to 08.2021) in PubMed, Scopus, Embase, Web of Science, Cochrane and Google Scholar databases was conducted, and 54 observational studies were included. Results: Systolic blood pressure (SBP) was found to be lower in the high adherence to MD group SMD: −0.08, (95%CI: −0.15, −0.02) whereas no differences regarding diastolic blood pressure (DBP) were observed between the high and low adherence to MD groups [SMD: −0.07, (95%CI: −0.13, 0.00)]. Mean DBP of all included studies for both high and low adherence groups were in healthy levels (<90 mmHg). Conclusions: Higher adherence to MD could positively influence SBP, but further research is needed in this field due to the heterogeneous definitions of low/high adherence and the type of studies used (observational).